Pengaruh Kepuasan Kerja dan Stres Kerja Terhadap Turnover Intention Karyawan CV. Berlian Sentosa Jakarta - Sheila Subaika Roy; Hendra Kurniawan; Syabrinildi Syabrinildi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine the effect of job satisfaction, and job stress on employee turnover intention at CV. Berlian Sentosa Jakarta. The population in this study were all employees of CV Berlian Sentosa. The number of samples in this study were 31 employees of CV. Berlian Sentosa using saturated sample technique. The data collection technique was carried out through distributing questionnaires, while this research method used quantitative methods. The results showed that (H1) Job satisfaction has a significant effect on turnover intention with t count job satisfaction -2.211 < 2.04841 and sig. 0,035 < 0,05. (H2) Job stress has a significant effect on turnover intention, namely with t count of job stress 4.705 > 2.04841 and the significance of the job stress variable 0.000 < 0.05. (H3) in the results of the F test is accepted with the value of F count 14,535> F table 3,340 and a significance value of 0.000 <0.05. In the results of the Coefficient of Determination (R2) with an R Square value of 0.509 which means Job Satisfaction and Job Stress have a contribution of 50.9% to Turnover Intention. Then the remaining 49.1% is influenced by other variables not included in this study.